Kepuasan Kerja Sebagai Pemediasi Pengaruh Kepemimpinan Melayani Terhadap Komitmen Organisasional - -, Utami Tunjung Sari; Bhenu Artha; Sulis (Jurnal Ilmiah Neraca : Ekonomi Bisnis, Manajemen, Akuntansi, 2025)
ABSTRACT Servant leadership is an approach that focuses on leadership from the leader's point of view and its behavior that emphasizes that leaders pay attention to the problems of their followers, empathize with them, and develop them and put followers first, empowering them, and helping them develop their personal capacities to the fullest. One of the results of a leader in influencing members in an organization is the organizational commitment of his followers. If the followers' commitment to the organization is high they will carry out their duties optimally. Organizational commitment is important for an organization in creating the survival of an organization. This research aims to analyze the influence of servant leadership on organizational commitment with job satisfaction as a mediator. The sample in this research is employees who work for organizations/companies who have worked for at least 1 year. This research uses primary data. The sampling technique in this research used purposive sampling. A total of 93 respondents participated in this research. The data collection tool used in this research is a questionnaire distributed online. The data in this study was processed using SPSS with multiple linear regression analysis methods. The results of the data analysis showed that service leadership behavior has a positive influence on organizational commitment. Furthermore, job satisfaction mediates the influence of service leadership on organizational commitment. These findings show that servant leadership increases job satisfaction and employees who have high job satisfaction with the organization have a tendency to have organizational commitment. Keywords: Servant Leadership; Servant Leadership; Job satisfaction